The Dual Role of Middlemen in Triwungan Village in the Utilization of Digital Technology to Improve the Economic Welfare of Tobacco Farmers - Laily Fitriya; Rizki Febri Eka Pradani (Darul Yasin Al Sys, 2026)
This study is motivated by the continuing dependence of tobacco farmers on middlemen for capital access, market information, and product distribution, despite the growing influence of digital technology on agricultural communication and marketing practices. This study aims to analyze the dual role of middlemen in Triwungan Village, Kotaanyar District, Probolinggo Regency, in utilizing digital technology and to examine its implications for the economic welfare of tobacco farmers. A qualitative approach with a descriptive design was employed. Data were collected through observation, in-depth interviews, and documentation, with informants selected using purposive sampling. The data were analyzed through reduction, presentation, and conclusion drawing, while validity was ensured through source and method triangulation. The findings indicate that middlemen perform a dual role not only as intermediaries in crop marketing but also as providers of capital, sources of market information, and key connectors within the tobacco distribution chain. The use of WhatsApp has accelerated communication and transaction processes; however, digitalization has not substantially altered the structural dependence of farmers on middlemen. Instead, it has strengthened the position of middlemen within the marketing system. Consequently, although farmers experience improved access to information and greater communication efficiency, their bargaining position remains relatively weak. This study concludes that digital technology, when embedded within unequal agrarian marketing relations, may reinforce intermediary dominance rather than automatically improve farmers’ economic independence. The findings contribute to a more contextual understanding of digitalization in rural agricultural economies and offer practical implications for strengthening farmer-centered market access, digital literacy, and bargaining capacity.